Developing Interactive PowerPoint for Teaching Vocabulary in Higher Education - Retnita Saputri; Indah Tri Purwanti; Atni Prawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research focuses on developing interactive PowerPoint materials using the ADDIE model of development. Employing the Research and Development (R&D) method, the research involved first-semester students from the English Study Program at Universitas Riau, Pekanbaru, who were enrolled in a Vocabulary course. Data were collected through a needs analysis questionnaire and expert judgment validation. A total of 38 students participated in the needs analysis. Expert validation was administrated from three domains: media, material, and pedagogy. The findings showed a preference for interactive PowerPoint as a learning media. The media validation results revealed “highly valid” scores: 85.5% for the "Food" topic and 92.7% for "Art and Literature." Material validation yielded a 96% score for both topics, while teaching validation showed a 90% score. These results suggest that interactive PowerPoint materials developed using the ADDIE model are highly valid.